Hotels and Tourism : Case Study of Kingston Hotel in Chow Kit, Malaysia - Septa Intiar; Ahmad Mansur; Umar Abdul Jabbar (An International Journal Tourism and Community Review, 2025)
This study aims to analyze the effect of service quality on customer satisfaction in the retail sector. The background of this study stems from the importance of service quality in improving customer satisfaction, which ultimately influences loyalty and purchasing decisions. In an increasingly competitive retail environment, customer satisfaction plays a pivotal role in shaping consumer behavior. The method used in this study is a survey with a quantitative approach, where data is collected through questionnaires distributed to 150 customer respondents across several retail stores. The collected data were analyzed using regression analysis techniques to test the relationship between service quality and customer satisfaction variables. The findings of this study indicate that service quality significantly influences customer satisfaction, with service speed and staff friendliness identified as the most dominant factors. These results highlight the essential role of service quality in driving customer satisfaction and suggest that retail businesses should prioritize enhancing these aspects of service to meet customer expectations. The implication of these findings is the importance for retail companies to continually improve service quality as a strategic approach to retain customers and increase their satisfaction. This study contributes to the development of service theory, providing insights into the dynamics between service quality and customer satisfaction. Additionally, it offers practical recommendations for managers in the retail sector, emphasizing the need for a customer-focused approach to enhance competitive advantage in the market.